SIGVerse: A Cloud-Based VR Platform for Research on Multimodal Human-Robot Interaction - Inamura, Tetsunari; Mizuchi, Yoshiaki (Frontiers in Robotics and AI, 2021)
Research on Human-Robot Interaction (HRI) requires much consideration on experiment design and much time to practice the subject experiment. Recent technology on virtual reality (VR) has the potential to deal with this time and effort. The significant advantages of VR systems to HRI are: 1) it enables cost reduction because we do not need to construct experimental facilities in a real environment, 2) it can provide the same environmental conditions and embodied interaction conditions to test subjects, 3) it is possible to visualize arbitrary information and situations that cannot occur in reality, such as playback of past experiences, and 4) it is easy to provide an immersive and natural interface for robot/avatar teleoperation. Although VR tools that have each feature have been used and developed in previous HRI research, no all-encompassing tools or frameworks have been available. In particular, the benefits of integration with cloud computing have not been considered in depth. The purpose of this paper is to propose a research platform that can comprehensively provide the necessary elements for HRI research by integrating VR and cloud technologies. To realize the flexible and reusable system, we develop a real-time bridging mechanism between ROS and Unity. We apply the proposed system to three case studies, including a robot competition named RoboCup@Home to confirm the feasibility of the system in a realistic HRI scenario. Through the case studies, we show the system's usefulness and potential for the development and evaluation of social intelligence through multimodal HRI.